Ce que le néolibéralisme fait au travail : une étude de cas en centre d’appels téléphoniques - Stéphane Le Lay; Duarte Rolo (Terrains/Théories)
In this article, the authors try to show how on one hand, the Foucauldian theses on neoliberalism can inform studies on the organization of work; on the other hand, to discuss these theses on the basis of an analysis of the real work of employees working in call centres. The clinical material collected through this survey provides a nuanced confirmation of Foucauldian theses. While some employees question the managerial mechanisms acting as a "conduct management" mechanism aimed at influencing ethical suffering, many of them participate in it openly.